Measuring Progress: A Review Essay on The Pricing of Progress: Economic Indicators and the Capitalization of American Life by Eli Cook - Coyle, Diane (Journal of Economic Literature, 2019)
There is growing interest in the history of economic statistics, and Eli Cook has provided in The Pricing of Progress: Economic Indicators and the Capitalization of American Life a fascinating account of the era of economic measurement prior to the creation of the modern System of National Accounts. The story illustrates the dual character of statistics, which is the product of political contestation and social structures, as well as the data by which we can interpret the economy. Appreciating this duality through the history of economic measurement helps explain why political polarization today often seems to play out as competing interpretations of the “facts.” In this context, the idea that GDP growth is a good measure of economic progress is increasingly being challenged, as both the “beyond GDP” agenda and digital disruption point to a growing wedge between what GDP is measuring and economic welfare. Economists should be engaging with the history of the statistics we use every day in order to be able to shape their future. (JEL C38, E01, E23, N10)